Development of a Predictive Model for Estimating Stocks of Medicinal Plants Using GIS Tools on the Example of the Middle Urals - Turyshev, A. Yu; Belonogova, V. D.; Luzhanin, V. G. (Razrabotka i registraciâ lekarstvennyh sredstv (Online), 2022)
Introduction. Intensive anthropogenic impact leads to a sharp reduction in natural reserves of many valuable plants. In this regard, previously obtained data on stocks quickly become obsolete. Therefore, the inventory of stocks of medicinal plants in the Russian Federation as a whole and the Middle Urals, in particular, remains an urgent problem. Unfortunately, modern technologies are not being implemented intensively enough in the domestic pharmacy. In our opinion, the reasons for this are expensive software, insufficient theoretical and practical skills to work on personal computers, as well as the specifics of the industry. Despite this, the use of geographic information systems (GIS) in pharmacy is quite promising [7–9]. The use of geographical information systems as a methodological basis will make it possible to map the areas of medicinal plants, to analyze plant communities not only for the territory of the Middle Urals at a high scientific level [1, 4]. Aim. Development of predictive models for the distribution of medicinal plants based on a comprehensive assessment of the state of populations of wild medicinal plants of the Middle Urals. Materials and methods. The determination of raw material reserves of the studied species of medicinal plants was carried out on specific thickets according to the generally accepted methodology. The authenticity of raw materials was established by the macroscopic method when collecting samples of raw materials. In the course of the study, stocks of 4652 populations of 27 species of medicinal plants growing in the Middle Urals were studied. The collection of the material was carried out in the period from 2006 to 2019 during the survey of the administrative districts of the Perm Krai and the Sverdlovsk region. A comparative comprehensive assessment of resource and phytochemical indicators was studied using the example of 6 species of wild medicinal plants: Origanum vulgare L., Lamiaceae , Hypericum perforatum L., Hypericaceae and Hypericum maculatum Crantz, Hypericaceae , Tanacetum vulgare L., Asteraceae , Artemisia absinthium L., Asteraceae , Leonurus quinquelobatus Gilib., Lamiaceae , Achillea millefolium L., Asteraceae . Results and discussion. In the course of resource and phytochemical studies of representatives of the medicinal flora of the Middle Urals, a comprehensive assessment of the state of populations of wild medicinal plants – sources of medicinal plant raw materials ( herba Origani vulgaris , herba Hyperici , flores Tanaceti vulgaris , herba Artemisiae absinthii , herba Achilleae millefolii and herba Leonuri ) was carried out. A geospatial analysis of the distribution of medicinal plant populations by soil types within the regions of the Middle Urals was carried out. An algorithm for constructing predictive models of the distribution of populations of wild medicinal plants of the Middle Urals has been worked out. A set of maps of the "occurrence" of medicinal plants in the study area has been developed. Conclusion. The conducted complex of studies will allow updating information about the medicinal flora of the Middle Urals. Developed on the example of a number of representatives of the medicinal flora of the Middle Urals, the algorithm for constructing forecast maps can be used for any regions in the presence of appropriate topos.